161k views
5 votes
3(x - 2) + 2 = 5(x - 3) + 9 por fa

User Ajt
by
5.4k points

1 Answer

4 votes

Answer:

x = 1

Explanation:

Given

3(x - 2) + 2 = 5(x - 3) + 9 ← distribute and simplify both sides

3x - 6 + 2 = 5x - 15 + 9

3x - 4 = 5x - 6 ( subtract 5x from both sides )

- 2x - 4 = - 6 ( add 4 to both sides )

- 2x = - 2 ( divide both sides by - 2 )

x = 1

User Jeanj
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.